Habitar somático: um corpo que abre os poros para ver (-se) a partir de sua dança/performance - Silva, Caroline Turchiello da (2016)
In the present work I seek to discuss about the body in performance as an experience that enables the spread of the ways to see / feel the self and the other. This is a research-art through a poetic on dance and performance art. I approach the performance as an artistic practice that allows to problematize the way how the bodies are built and the ways of looking and being looked at by those bodies that are made. Therefore I seek an approximation of areas of knowledge like Somatic Education and Visual Culture Studies. The first one besides being used as a body preparation during the research, allows important reflections about the body opposing dichotomy body and mind, admitting to be expanded proprioception, perception and with them the expressiveness. The second area with regard to the images that are produced in the performative acts, as well as those that were chosen-(re)created in the present work. Images that are capable to affect the subject that produces them as well as the one who allows her/himself to be affected by them. The development of performances and the reflection about them is the motto of the work for which the experience is established. In this way, the methodology of the work admitted the practice as a research, that is why, i use the assumptions of Somatic-Performative Research, formulated by Fernandes (2012, 2014, 2015). Thus, the textual elaboration triggered a performative writing that aims to present the methodological paths followed in the investigative process.